Public sector accounting education and training as supportive mechanisms of the ongoing accrual-based accounting reforms - Jafi, Hanane; Youssef, Said (Technium Social Sciences Journal, 2021)
This article explores the major challenges surrounding the ongoing wave of public sector accrual accounting reforms. In particular, this paper sheds light on the importance of training and skill development as essential components of capacity-building and discusses the crucial role educational institutions play in laying the basis of a sound Public Sector Accounting (PSA) body of knowledge. The article also provides recommendations based on studies and reports conducted by international organizations, standards-setting bodies, and accountancy profession institutions as well as capitalizing on the experience of leading countries in the public financial management field